Synthesis, Spectral and Biological Studies on Novel Schiff Base Complexes of [Manganese(II), Copper(II), Nickel(II) and Cobalt(II)] Derived from 3-Chloro Benzohydrazide and Aldehyde Drivative - Pal Singh, Netra; Kumar, Pradeep; Singh, Jagvir (Asian Journal of Chemistry, 2012)
The novel Schiff base complexes of the type [M'(L)2]Cl2/[M(L)2Cl2] where M = Mn(II), Ni(II), Co(II) and M' = Cu(II), L = N'-(4-chlorobenzoyl)-3-hydroxy-5-methoxy benzaldehyde hydrazone have been synthesized and characterized by various physico-chemical techniques (IR, NMR spectra, UV/visible spectra, EPR and CV studies). All the metals are coordinated in an octahedral geometry except copper(II) complex. Copper(II) complex is coordinated in square planar geometry. All the newly synthesized compounds were screened for their antimicrobial activity. Some of the compounds exhibited significant inhibition on bacterial and fungal growth as compared to standard drugs.